Limited Dispersal and Significant Fine - Scale Genetic Structure in a Tropical Montane Parrot Species - Klauke, Nadine; Schaefer, H. Martin; Bauer, Michael; Segelbacher, Gernot (PLOS ONE, 2016)
Tropical montane ecosystems are biodiversity hotspots harbouring many endemics that are confined to specific habitat types within narrow altitudinal ranges. While deforestation put these ecosystems under threat, we still lack knowledge about how heterogeneous environments like the montane tropics promote population connectivity and persistence. We investigated the fine-scale genetic structure of the two largest subpopulations of the endangered El Oro parakeet (Pyrrhura orcesi) endemic to the Ecuadorian Andes. Specifically, we assessed the genetic divergence between three sites separated by small geographic distances but characterized by a heterogeneous habitat structure. Although geographical distances between sites are small (3–17 km), we found genetic differentiation between all sites. Even though dispersal capacity is generally high in parrots, our findings indicate that dispersal is limited even on this small geographic scale. Individual genotype assignment revealed similar genetic divergence across a valley (~ 3 km distance) compared to a continuous mountain range (~ 13 km distance). Our findings suggest that geographic barriers promote genetic divergence even on small spatial scales in this endangered endemic species. These results may have important implications for many other threatened and endemic species, particularly given the upslope shift of species predicted from climate change.